2016
DOI: 10.2166/wst.2016.320
|View full text |Cite
|
Sign up to set email alerts
|

The study of non-linear kinetics and adsorption isotherm models for Acid Red 18 from aqueous solutions by magnetite nanoparticles and magnetite nanoparticles modified by sodium alginate

Abstract: Azo dyes are widely used in various industries. These substances produce toxic byproducts in aquatic environments in addition to their mutagenic and carcinogenic potential effects. In this study, the effect of magnetite nanoparticles and magnetite nanoparticles modified by sodium alginate in batch systems and nonlinear kinetic and adsorption isotherm models were investigated. Magnetite nanoparticles were synthesized by chemical co-precipitation method and then modified and used as adsorbent to adsorb Acid Red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…NaAlg is a negatively charged biodegradable polysaccharide that is extracted from brown seaweed. The phenomenal properties of the low‐cost NaAlg are biocompatibility, nontoxicity, and its biological origin . To generate antimicrobial properties in blended polymer solutions, the incorporation of metallic nanoparticles is required, such as silver nanoparticles (Ag‐NPs) and ZnO‐NPs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NaAlg is a negatively charged biodegradable polysaccharide that is extracted from brown seaweed. The phenomenal properties of the low‐cost NaAlg are biocompatibility, nontoxicity, and its biological origin . To generate antimicrobial properties in blended polymer solutions, the incorporation of metallic nanoparticles is required, such as silver nanoparticles (Ag‐NPs) and ZnO‐NPs .…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenal properties of the low-cost NaAlg are biocompatibility, nontoxicity, and its biological origin. [19][20][21] To generate antimicrobial properties in blended polymer solutions, the incorporation of metallic nanoparticles is required, such as silver nanoparticles (Ag-NPs) and ZnO-NPs. [22][23][24][25] The ZnO-NPs metallic nanoparticles enhance water permeability, antibacterial activity, and metal uptake capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The result clearly showed that Langmuir isotherm amongst the other isotherms studied, best described the adsorption of Cd(II) and Cr(VI) ions with higher correla-tioncoefficientR 2 (>0.99), followed by Dubinin-Radushkevich, Temkin, and Freundlich model, respectively. In addition, this assertion was further justified with lower values of chi-square (χ 2 ), the sum of square error (ERRSQ/SSE), and the sum of absolute error (EABS), obtained when compared with the order models indicating the closeness of the model experimental results to the calculated results obtained [36,37,38]. This finding is similar to the results obtained on the sorption of cadmium and hexavalent chromium from electroplating wastewater [23] and non-linear prediction of kinetic and equilibrium data for the adsorption of hexavalent chromium by carbon materials [39].…”
Section: Isotherms Adsorption Studymentioning
confidence: 76%
“…∆S<0, it shown that the adsorption process was a process of decreasing entropy. Studies have shown (Berizi et al 2016;Mao et al 2018) that when the absolute value of ∆G is less than 20 kJ•mol -1 , the adsorption is physical adsorption; when the absolute value of ∆H is within the range of 2~29kJ/moL, the force between the adsorbent and the solute is dominated by hydrogen bonding. It can be seen from Table 5 that the absolute value of ∆G during the adsorption process of the LAD hydrogel adsorbent on AR 73 was 4.494~6.247 kJ•moL -1 , and the absolute value of ∆H was 23.640 kJ•moL -1 .It shown that there was hydrogen bond in the adsorption process of LAD on AR 73 in addition to physical adsorption.…”
Section: Study On Adsorption Thermodynamicsmentioning
confidence: 99%